Isolation of Leishmania promastigote flagella - Beneke, T; Demay, F; Wheeler, RJ; Gluenz, E (Humana Press, 2020)
Eukaryotic flagella are conserved multifunctional organelles with roles in motility, intercellular interactions and signal transduction. Leishmania possess a single flagellum at all stages of their life cycle. Flagella of promastigote forms in the fly are long and motile, with a canonical 9+2 microtubule axoneme and an extra-axonemal paraflagellar rod (PFR). This protocol describes a simple method for the isolation of Leishmania mexicana promastigote flagella, optimised to yield intact flagella that retain both the cytoskeletal elements (9+2 axoneme and PFR) and the surrounding membrane. The isolated flagella and deflagellated cell bodies are suitable for analysis by electron microscopy, protein mass spectrometry and lipidomics.